2018
DOI: 10.3390/ijms20010106
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Adipose Tissue-Enhanced Vasodilation in Metabolic Syndrome Rats by Apelin and N-Acetyl–l-Cysteine-Sensitive Factor(s)

Abstract: Perivascular adipose tissue (PVAT) can regulate vascular tone. In mesenteric arteries of SHRSP.Z-Leprfa/IzmDmcr rats (SHRSP.ZF) with metabolic syndrome, vascular dysfunction is compensated by PVAT-dependent mechanisms that disappear with increasing age. In this study, we investigated the mechanisms of the age-related changes and responsible factor(s) involved in the enhancing effects of mesenteric arterial PVAT in SHRSP.ZF. Acetylcholine- and sodium nitroprusside-induced relaxations of isolated arteries were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…PVAT has been recognized to regulate vascular tone via releasing important adipokines. Apelin is one of these important adipokines (Kagota et al 2019). Kagota and collegues reported that the vasorelaxant effect level of apelin was higher in the presence of PVAT.…”
Section: Discussionmentioning
confidence: 99%
“…PVAT has been recognized to regulate vascular tone via releasing important adipokines. Apelin is one of these important adipokines (Kagota et al 2019). Kagota and collegues reported that the vasorelaxant effect level of apelin was higher in the presence of PVAT.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment started at 13 weeks of age ( T 0 ) and continued for 10 consecutive weeks. The age range of animals was chosen based on the studies showing that the “breakdown” of the PVAT compensatory system occurs at 23 weeks of age, 16,17 while the specific doses of tofogliflozin were previously used in Zucker diabetic rats and db/db mice. 6 Rats were provided a standard chow diet (CE-2; Clea Japan Inc., Tokyo, Japan) and water ad libitum during the experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that the PVAT around the mesenteric arteries compensates for the effects of impaired nitric oxide (NO)-dependent vasodilation on the circulatory system, a condition that develops when these rats reach 17 and 20 weeks of age, but this compensatory function disappears as MetS progresses (around 23 and 30 weeks of age). 16,17 We have also reported that aged SHRSP.ZF rats exhibit ventricular diastolic dysfunction 18,19 and investigated the potential mechanisms underlying the deterioration of PVAT compensatory function associated with the development of cardiac dysfunction in MetS. We also reported that angiotensin II type I receptor antagonists (ARBs), including azilsartan, telmisartan, and olmesartan, protect against MetS-associated vascular and cardiac dysfunction in SHRSP.ZF rats.…”
Section: Introductionmentioning
confidence: 99%
“…In rats, aging reportedly attenuated the anti-contractile effect of PVAT around the thoracic aorta, while reducing the amount of brown adipose tissue-like PVAT ( 59 ). In the mesenteric arteries of SHRSP.Z-Leprfa/IzmDmcr rats (SHRSP.ZF) with metabolic syndrome, vascular dysfunction is compensated by a PVAT-dependent mechanism, which disappears with age ( 60 ). Compared with young C57BL/6JRj mice, middle-aged mice showed more PVAT hypertrophy ( 61 ); furthermore, the mean single adipocyte area in PVAT was significantly increased, while the expression level of protein inhibitor of activated signal transducer and activators of transcription 1 (a key negative regulator of inflammation) was decreased.…”
Section: Roles Of Pvat In Vascular Diseasementioning
confidence: 99%